2005
DOI: 10.1080/02791072.2005.10400520
|View full text |Cite
|
Sign up to set email alerts
|

Native Women, Violence, Substance Abuse and HIV Risk

Abstract: Violence has become a critical public health issue in the United States. It has had a particularly devastating impact on the health and well being of Native American women and children. The relationship between aggression and substance use is an intrinsic one: Native women often bear the brunt of violence in drinking situations, which places them and their children at extremely high risk for physical and sexual abuse. In urban environments, many Native American women find themselves in adult relationships that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 18 publications
1
18
0
2
Order By: Relevance
“…Although studies have indicated a link between socioeconomic status and GBV [98][99][100], GBV is by no means confined to people living in poverty. Incarceration [101], minority [24,52,60,102] and migrant [103] status or relocation [104] are similarly linked, as is substance abuse [105,106], or a co-occurrence of these contexts [107][108][109]. Almost all of these studies are from the United States.…”
Section: Transactional Sexmentioning
confidence: 95%
“…Although studies have indicated a link between socioeconomic status and GBV [98][99][100], GBV is by no means confined to people living in poverty. Incarceration [101], minority [24,52,60,102] and migrant [103] status or relocation [104] are similarly linked, as is substance abuse [105,106], or a co-occurrence of these contexts [107][108][109]. Almost all of these studies are from the United States.…”
Section: Transactional Sexmentioning
confidence: 95%
“…Considerable progress has been made toward understanding the issue; however, it is only recent that research on substance abuse related to women has been recognized as being sorely neglected (Leshner 1998). Studies show that women who abuse substances have problems related to co-dependency, incest, physical and sexual abuse, victimization, sexuality and relations with significant others (Bohn 2003;Freeman et al 2002;Saylors and Daliparthy 2005;Straussner and Brown 2002). A particular stressful event is often cited by women as a reason for initiating the use of harmful drugs; and, many female substance abusers report being victims of childhood physical and/or sexual abuse (Gil-Rivas et al 1996;Haller and Miles 2004;Rosen et al 2002;Simpson and Miller 2002).…”
Section: Introductionmentioning
confidence: 96%
“…This series of studies includes research on 490 adult substance abusers, women and men, who received treatment from 2003-2008 and completed both a baseline and six-month follow-up questionnaire, regardless of whether or not they completed the prescribed course of treatment (Wright et al 2011;Saylors & Daliparthy 2005;Saylors 2003;CSAT 1999). The results in this section pertain to several CSAT projects that included the Native Women's Circle and Native Men's Circle with a target population of adult substance abusers.…”
Section: Native Men and Native Womenmentioning
confidence: 99%